Preparation of reversible photoresponsive N-hydroxyethyl spiropyran/polyacrylonitrile fiber materials with mechanical stability by electrospinning for regulating wettability and humidity automatically. (November 2019) - Wang, Caifeng; Liu, Zhenfu; Li, Chunhao; Wu, Yun; Wang, Shuai
Novel photoresponsive N-hydroxyethyl spiropyran (SP-OH)/polyacrylonitrile (PAN) fiber materials with reversible changes in wettability and humidity were prepared by electrospinning in this work. SP-OH and PAN were mixed through a physical doping method. The wettability and humidity regulation of the electrospun films can be reversibly manipulated by the simple change of ultraviolet (UV)-visible (UV-Vis) light irradiation due to the photoisomerization mechanism of the spiropyran chromophore. Under UV light irradiation, SP-OH molecules exhibit a colored polar open-ring status, resulting in electrostatic attraction with water. However, under visible light irradiation, they are colorless and nonpolar and lose the attraction effect. Wettability and ambient humidity were regulated by this repeated transformation between polar surface and nonpolar surface. The tensile strength and the reversible change ranges of wettability and humidity under UV-Vis irradiation are all closely related to the doping amount of SP-OH. Electrospinning is a promising method to achieve large-scale production that can put such a material into practical application.